Fekete-Szegö Inequality for a Subclass of Bi-Univalent Functions Linked to q-Ultraspherical Polynomials (Contemporary Mathematics, 2024)
In this study, we introduce a new class of bi-univalent functions using q-Ultraspherical polynomials. We derive the Fekete and Szegö functional problems for functions in this new subclass, as well as estimates for the Taylor-Maclaurin coefficients |α2| and |α3|. Furthermore, a collection of fresh outcomes is presented by customizing the parameters employed in our initial discoveries.
Keywords: analytic functions, subordination, orthogonal polynomial, q-Ultraspherical polynomials, Fekete-Szegö problem, quantum calculus, univalent, bi-univalent functions